Familias en el siglo XXI: realidades diversas y políticas públicas - Flores Celis, Karla (El Colegio de México A.C., 2012)
This text summarizes the interventions during the presentation of Families in the 21st Century: Diverse realities and public policies at El Colegio de México. This publication compiles articles from the seminar of the same name held two years earlier to analyze the problem of family diversity and its link with public policies in Mexico from an academic point of view, while maintaining a framework of plurality and dialogue with various actors in society.